Romesh Chandra, President of the World Peace Council will give a report… (U.S. Peace Council, New Haven Chapter)
All text, black lettering on yellow sheet Poster advertising a talk by Romesh Chandra at the Yale Law School on the proceedings of the World Parliament of People for Peace, Madrid Meetings and United Nations General Assembly PO-1316